Social Determinants of Health and Uncontrolled Blood Pressure in a National Cohort of Black and White US Adults: the REGARDS Study - Akinyelure, Oluwasegun P; Jaeger, Byron C; Oparil, Suzanne; Carson, April P; Safford, Monika M; Howard, George; Muntner, Paul; Hardy, Shakia T (Hypertension (Dallas, Tex. 1979), 2023)
Determining the contribution of social determinants of health (SDOH) to the higher proportion of Black adults with uncontrolled blood pressure (BP) could inform interventions to improve BP control and reduce cardiovascular disease. We analyzed data from 7306 White and 7497 Black US adults taking antihypertensive medication from the REGARDS (Reasons for Geographic and Racial Differences in Stroke) study (2003-2007). SDOH were defined using the Healthy People 2030 domains of education, economic stability, social context, neighborhood environment, and health care access. Uncontrolled BP was defined as systolic BP ≥140 mm Hg or diastolic BP ≥90 mm Hg. Among participants taking antihypertensive medication, 25.4% of White and 33.7% of Black participants had uncontrolled BP. The SDOH included in the current analysis mediated the Black-White difference in uncontrolled BP by 33.0% (95% CI, 22.1%-46.8%). SDOH that contributed to excess uncontrolled BP among Black compared with White adults included low annual household income (percent-mediated 15.8% [95% CI, 10.8%-22.8%]), low education (10.5% [5.6%-15.4%]), living in a health professional shortage area (10.4% [6.5%-14.7%]), disadvantaged neighborhood (11.0% [4.4%-18.0%]), and high-poverty zip code (9.7% [3.8%-15.5%]). Together, the neighborhood-domain accounted for 14.1% (95% CI, 5.9%-22.9%), the health care domain accounted for 12.7% (95% CI, 8.4%-17.3%), and the social-context-domain accounted for 3.8% (95% CI, 1.2%-6.6%) of the excess likelihood of uncontrolled BP among Black compared with White adults, respectively. SDOH including low education, low income, living in a health professional shortage area, disadvantaged neighborhood, and high-poverty zip code contributed to the excess likelihood of uncontrolled BP among Black compared with White adults.